The German occupation authorities’ treatment of national and religious minorities in Gdańsk Pomerania (1939–1945) - Sziling , Jan (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the policy of the German authorities toward national and religious minorities living in Pomerelia during the Second World War. The aim of the study is to demonstrate how various ethnic groups were treated by the occupation administration and to explain the motives behind this policy. The research is based on the analysis of administrative documents, police records, and sources concerning the functioning of the Reichsgau Danzig–West Prussia. The author presents the ethnic structure of the region before the outbreak of the war, noting the predominance of the Polish population alongside German, Jewish, Ukrainian, Belarusian, and other ethnic minorities. The analysis demonstrates that the German occupation led to radical demographic changes through extermination, expulsions, and Germanization policies. Particularly brutal measures were directed against Jewish and Roma populations, whose persecution stemmed from the racist assumptions of Nazi ideology. Certain East Slavic minorities, such as Ukrainians, Belarusians, and Russians, were treated differently and were considered potentially useful for political purposes. The author emphasizes the importance of the police and security apparatus as the principal instrument for implementing nationality policy. The conclusions indicate that the occupiers’ actions were subordinated to both racial and political objectives, resulting in a profound transformation of the region’s ethnic structure and the marginalization or destruction of many minority communities.